(untitled) (Research, Society and Development, 2018)
This study sought to understand the preceptors’ view of a multiprofessional integrated health program with emphasis on onco-hematology in a large oncology hospital in southern Brazil. This is a qualitative, exploratory study with quantitative variables. Data generation was performed through the focal group technique, recorded in audio and the application of a questionnaire. The collected data were submitted to content thematic analysis, according to Bardin. The results demonstrate the multiprofessional residence as an institution of collective spaces for the construction of interdisciplinary knowledge. In addition, infrastructure conditions are highlighted as positive sources for developing practical activities. However, readjustments are suggested in the pedagogical project of the course, in search of an interdisciplinarity with greater effectiveness, in order to improve the theoretical-practical articulation. The importance of constant evaluations of the program in the different professional visions of the actors involved is also highlighted.